(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Due to the high incidence of tuberculosis (TB) in Indonesia, evaluating important factors of the TB patients’ quality of life is crucial. Individual-level factors play an essential role in enabling TB patients to manage their perceived needs and treatments to sustain the Quality of Life (QoL). Yet little is known about the relationships between individual-level factors and the QOL of TB patients in Indonesia. This study aimed to evaluate the association between individual-level factors (physical health, emotional state, social support, spirituality) and quality of life in TB patients. Methods: A cross-sectional study was conducted using a simple random sampling strategy, 73 TB patients were chosen based on their availability during data collection, and consent to participate in the study. The data were collected from a community sample of Surabaya City, East Java, Indonesia. In the present study, the following instruments were used: Early Warning Score System (EWSS), Depression Anxiety Stress Scale (DASS)-21, MOS Social Support Survey-14, Daily Spiritual Experience Scale (DSES), and the World Health Organization Quality of Life (WHO-QoL). Spearman’s rank correlation coefficient was used to discover the association between variables. Results and Discussions: The results showed that there were significant relationships between physical health (p = 0.037), emotional state (p = 0.04), social support, spirituality and QoL (p = 0.001). Conclusion: In conclusion, individual-level factors associated with TB patients’ quality of life: physical health, emotional state, social support, and spirituality.